Probing conventional and new physics at the ESS with coherent elastic neutrino-nucleus scattering - Ayan Chattaraj; Anirban Majumdar; Dimitrios K. Papoulias; Rahul Srivastava (Journal of High Energy Physics)
Abstract We explore the potential of the European Spallation Source (ESS) in probing physics within and beyond the Standard Model (SM), based on future measurements of coherent elastic neutrino-nucleus scattering (CEνNS). We consider two SM physics cases, namely the weak mixing angle and the nuclear radius. Regarding physics beyond the SM, we focus on neutrino generalized interactions (NGIs) and on various aspects of sterile neutrino and sterile neutral lepton phenomenology. For this, we explore the violation of lepton unitarity, active-sterile oscillations as well as interesting upscattering channels such as the sterile dipole portal and the production of sterile neutral leptons via NGIs. The projected ESS sensitivities are estimated by performing a statistical analysis considering the various CEνNS detectors and expected backgrounds. We find that the enhanced statistics achievable in view of the highly intense ESS neutrino beam, will offer a drastic improvement in the current constraints obtained from existing CEνNS measurements. Finally, we discuss how the ESS has the potential to provide the leading CEνNS-based constraints, complementing also further experimental probes and astrophysical observations.